IMPLEMENTATION OF DISCIPLINE CHARACTER EDUCATION WITH CONTEXTUALTEACHING LEARNING (CTL) MODEL IN LEARNING AT STATE 1ST ELEMENTARY SCHOOL OF ADIKARSO KEBUMEN - Afrida Conniestia Ikhsani; Nadya Vera Wibowo; Purwaka Atmaja; Rokhmaniyah Rokhmaniyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Character education nowadays is an important thing to do because of the widespread moral crisis among the community, it is from children, adolescents to adults. For this reason, it is necessary to improve a character education as early as possible from various communities. The characters that need to be developed are discipline. This article describes the results of research that aims to explain the character of discipline in relation to contextual models that can be seen from the influence of the use of contextual models in learning in elementary schools. This study uses a qualitative approach which is carried out with data collection techniques through observation, interviews and questionnaires. The sample of this study was the second and fifth grade students at Adikarso 1 Elementary School. To maintain the quality of the data, this study uses triangulation techniques. The results showed in the table of class II, before learning the percentage of students who answered "always" amounted to 80.345% while after learning rises to 86.551%. It can be concluded that the contextual learning model can improve the character of discipline in learning at SDN 1 Adikarso.